(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The influence of saturated with tetraphenylhydrazine (TPhH) micelles on the rate of diphenylamine reaction with potassium persulfate has been studied. It is shown that the rate of accumulation of a reaction product in presence of preliminary saturated with TPhH micelles decreases less in comparison with non- treated with TPhH micelles. Obtained results confirm our early assumption that located in a hydrophobic nucleus of micelles TPhH is spatially separated with persulfate, and the process of diphenylamine oxidation stops on stage 1.